Lung respiration and muscular locomotion of Lymnaea stagnalis at chronic acidification of environment - Shahrani, Mohamed; Sidorov, Alexander V. (Experimental Biology and Biotechnology, 2017)
In experiments on molluscs is assumed that weekly incubation of animals in aquariums with water pH level at 6.3 units, results in intensification of lung respiration, accompanied by its duration (1.5-time) and frequency (1.4-time) increase, as well as in equivalent rise of locomotion speed (on 3rd day after the beginning of experiments). On seventh day of incubation, locomotion speed became the same in comparison with control group (incubation in aquariums with water pH level at 7.3 units). We suggest that mentioned above differences are due to the different sensitivity of dopamine- and serotonin containing neurons and synapses, which are involves in motor control of lung respiration and muscular locomotion respectively, to interstitial pH level.
Keywords: molluscs; behavior; acid-base balance (pH); fresh water ecology; adaptation